If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x=42+3x
We simplify the equation to the form, which is simple to understand
9x=42+3x
We move all terms containing x to the left and all other terms to the right.
+9x-3x=+42
We simplify left and right side of the equation.
+6x=+42
We divide both sides of the equation by 6 to get x.
x=7
| 1-(-26j)=-987 | | 6/x+5/2x=6 | | 5(x-1)=2x+3 | | 115/900 | | -4+10v=36 | | 18-4*3=8*3/4 | | 4(2x+5)=2(4x+10) | | -3x+18=-39 | | 265=z/11-236 | | -0.6x+0.7x+5=-7 | | -0.61-(-7.74)= | | 8+-(3)= | | 6x-1=5x-17 | | -7/8u=-49 | | 6(2y-3)=102 | | z^2+z+17=0 | | 5t+115=570 | | 6(2x-3)=102 | | X+0.08x= | | 2x-3=102 | | 15=-7-a/6 | | -15=-5/3x | | 3s-13s=80 | | X+0.08x=135 | | 15=-7-(a/6) | | 12=-2/5w | | 12=-2/5w | | 4(-2)(-1)(-4)= | | 6x=71/5 | | (-9y)2= | | 8x-9x=-2 | | -14x-9=-14x-15 |